Application of protein knockdown strategy targeting β-sheet structure to multiple disease-associated polyglutamine proteins. Issue 1 (1st January 2020) - Yamashita, Hiroko; Tomoshige, Shusuke; Nomura, Sayaka; Ohgane, Kenji; Hashimoto, Yuichi; Ishikawa, Minoru
Graphical abstract: Abstract: Polyglutamine diseases are a class of neurodegenerative diseases associated with the accumulation of aggregated mutant proteins. We previously developed a class of degradation-inducing agents targeting the β-sheet-rich structure typical of such aggregates, and we showed that these agents dose-, time-, and proteasome-dependently decrease the intracellular level of mutant huntingtin with an extended polyglutamine tract, which correlates well with the severity of Huntington's disease. Here, we demonstrate that the same agents also deplete other polyglutamine disease-related proteins: mutant ataxin-3 and ataxin-7 in cells from spino-cerebellar ataxia patients, and mutant atrophin-1 in cells from dentatorubral-pallidoluysian atrophy patients. Targeting cross-β-sheet structure could be an effective design strategy to develop therapeutic agents for multiple neurodegenerative diseases.